A combination of HLA-DP α and β chain polymorphisms paired with a SNP in the DPB1 3’ UTR region, denoting expression levels, are associated with atopic dermatitis - Margolis, David J.; Duke, Jamie L.; Mitra, Nandita; Berna, Ronald A.; Hoffstad, Ole J.; Wasserman, Jenna R.; Dinou, Amalia; Damianos, Georgios; Kotsopoulou, Ioanna; Tairis, Nikolaos; Ferriola, Deborah A.; Mosbruger, Timothy L.; et al. (Frontiers in Genetics, 2023)
Components of the immune response have previously been associated with the pathophysiology of atopic dermatitis (AD), specifically the Human Leukocyte Antigen (HLA) Class II region via genome-wide association studies, however the exact elements have not been identified. This study examines the genetic variation of HLA Class II genes using next generation sequencing (NGS) and evaluates the resultant amino acids, with particular attention on binding site residues, for associations with AD. The Genetics of AD cohort was used to evaluate HLA Class II allelic variation on 464 subjects with AD and 384 controls. Statistically significant associations with HLA-DP α and β alleles and specific amino acids were found, some conferring susceptibility to AD and others with a protective effect. Evaluation of polymorphic residues in DP binding pockets revealed the critical role of P1 and P6 (P1: α31M+(β84G or β84V) [protection]; α31Q+β84D [susceptibility] and P6: α11A+β11G [protection]) and were replicated with a national cohort of children consisting of 424 AD subjects. These findings lay the foundation for evaluating non-self-antigens suspected to be associated with AD as they potentially interact with particular HLA Class II subcomponents, forming a complex involved in the pathophysiology of AD. Independently, AD susceptibility-associated residues were associated with the G polymorphism of SNP rs9277534 in the 3’UTR of the HLA-DPB1 gene, denoting higher expression of these HLA-DP alleles, while protection-associated residues were associated with the A polymorphism, denoting lower expression. It is possible that a combination of structural HLA-DP components and levels of expression of these components contribute to AD pathophysiology.